CompTIA Linux+ XKO-002. - Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"The CompTIA Linux+ Training Course includes expert instructor-led training modules with customized presentations, practice exam simulators and learning supplements for an all-inclusive training program that provides all the benefits of classroom training at your own pace. CompTIA's Linux+ is a is a vendor-neutral certification that validates the knowledge of individuals with a minimum of six to twelve months of practical Linux experience. The CompTIA Linux+ Course confirms an IT professional's proficiency in the everyday management of Linux-based clients and basic management of server systems. Students will learn the knowledge and tools necessary to manage Linux systems from the command line, as well as how to manage user administration, file permissions, software configurations, and Linux-based clients, server systems and security. This Linux+ training course follows the CompTIA objectives, ensuring you receive the training and knowledge needed to succeed."--Resource description page.
Title from resource description page (Safari, viewed May 25, 2017).
Keywords: Linux -- Examinations -- Study guides; Operating systems (Computers) -- Examinations -- Study guides; Computer networks -- Examinations -- Study guides; Electronic data processing personnel -- Certification; Electronic books